2017
DOI: 10.1186/s13638-017-0930-3
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive wireless sensor network reliability metric for critical Internet of Things applications

Abstract: Evaluating the reliability of a wireless sensor network (WSN) deployment is a highly important task especially when the WSN is used for a critical Internet of Things (IoT) application. In this paper, we introduce a novel comprehensive reliability metric to evaluate the reliability of WSN deployments over their intended mission time. Unlike the existing studies on the topic, the proposed metric takes into account that sensor nodes (SNs) are multi-component systems that are subject to different component failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…The authors assessed reliability for different WSN routing protocols while considering the battery level as the key reliability metric. The authors of [ 20 ] used a combinatorial approach to compute the reliability of a WSN for more realistic scenarios of failures. In their work, they used more reliability metrics: processor, sensor, transceiver and battery failures.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors assessed reliability for different WSN routing protocols while considering the battery level as the key reliability metric. The authors of [ 20 ] used a combinatorial approach to compute the reliability of a WSN for more realistic scenarios of failures. In their work, they used more reliability metrics: processor, sensor, transceiver and battery failures.…”
Section: Related Workmentioning
confidence: 99%
“…The authors in [ 19 , 20 ] investigated an aspect of the perception layer according to our suggested architecture. Although in [ 20 ] we can observe more realistic assumptions, both of the works provided solutions that are context dependent.…”
Section: Related Workmentioning
confidence: 99%
“…Certainly, the evaluation of sensor reliability is a highly important task, especially for Internet of Things (IoT) applications, and new performance indices need to be proposed [54]. Some recommendations for the standardized evaluation of sensor reliability are given in [55].…”
Section: Reliability Of Sensors In Cyber-physicals Systems a Brief Smentioning
confidence: 99%
“…The camera networks, as a kind of wireless sensor networks, have received considerable attention due to the potential value for the practical applications [1][2][3][4]. One of the most important applications of camera networks is person re-identification (re-ID) which is an issue of searching the same person from one camera sensor across different camera sensors with a probe image.…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, a lot of efforts expect to develop discriminative feature representations that are robust to the changes in views, pose, and illumination. Gray and Tao [5] proposed the Ensemble of Localized Features (ELF), each of *Correspondence: zhong.zhang8848@gmail.com 1 Tianjin Key Laboratory of Wireless Mobile Communications and Power Transmission, Tianjin Normal University, Tianjin, China 2 College of Electronic and Communication Engineering, Tianjin Normal University, Tianjin, China which consisting of a feature channel, location, and binning information, to overcome the viewpoint changes. Bazzani et al [6] presented the Symmetry-Driven Accumulation of Local Features (SDALFs) which considers symmetry and asymmetry perceptual principles to handle the environmental variances.…”
Section: Introductionmentioning
confidence: 99%